The Media Activism of Latin America's Leftist Governments: Does Ideology Matter? - Philip Kitzberger (German Institute of Global and Area Studies (GIGA), 2010)
Has Latin America's left turn mattered in media politics? Does ideology impact governments' practices and policies regarding media and journalistic institutions? Through an empirical assessment of discourses on the media, of direct-communication practices, and of media regulation policies on the part of the recent leftist governments of Argentina, Bolivia, Brazil, Chile, Ecuador, Uruguay, and Venezuela, this paper stresses the existence of a specific media activism on the part of leftist governments in Latin America. While showing that the current binary distinctions that stress the existence of two lefts - 'populist' and 'nonpopulist' - obscure important commonalities and continuities, the author also demonstrates that it is the existence of certain institutional and structural constraints that best accounts for the differ-ences among the various leftist governments in Latin America. In sum, the paper challenges the prevailing neglect of ideology as a relevant factor in explaining developments in government-media relationships in the region. – – Hat sich Lateinamerikas Linksruck auf die Medienpolitik ausgewirkt? Hat Ideologie auf die Politik und Einstellung der Regierungen gegenüber Medien und Presse einen Einfluss? Durch eine empirische Feststellung von öffentlichen Regierungsmediendiskursen, direkten Kommunikationsvorrichtungen und Medienregulierungspolitik in den jüngsten linksorientierten Regierungen in Argentinien, Bolivien, Brasilien, Chile, Ecuador, Uruguay und Venezuela, hebt diese Arbeit die Existenz eines spezifischen Medienaktivismus der regionalen Linksregierungen hervor. Während gezeigt wird, dass binarische Unterscheidungen zwischen einer 'populistischen' und einer 'nichtpopulistischen' Linken wichtige Gemeinsamkeiten und Kontinuitäten verdunkeln, belegt die Arbeit, dass, jenseits der Gemeinsamkeiten, das Vorhandensein gewisser Zwangskontexte die Unterschiede zwischen den verschiedenen linken Regierungserfahrungen in Lateinamerika besser erklärt. Diese Arbeit stellt somit die herrschende Vernachlässigung von Ideologie als relevantem Faktor für die Erklärung der regionalen Verhältnisse zwischen Regierungen und Medien in Frage.
Keywords: 300; media; journalism; Latin America; government; ideology; leftismdien in Frage.